2018
DOI: 10.3390/ma11040571
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Approach for Evaluating the Contraction of Hypo-Peritectic Steels during Initial Solidification by Surface Roughness

Abstract: The contraction of peritectic steels in the initial solidification has an important influence on the formation of surface defects of continuously cast slabs. In order to understand the contraction behavior of the initial solidification of steels in the mold, the solidification process and surface roughness in a commercial hypo-peritectic and several non-peritectic steels were investigated using Confocal Scanning Laser Microscope (CSLM). The massive transformation of delta-Fe (δ) to austenite (γ) was documented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 36 publications
0
3
0
2
Order By: Relevance
“…It may depend on the large surface roughness of peritectic steel. The research of Guo [ 27 ] showed that during the solidification of steel, the peritectic reaction causes the surface shrinkage of the δ phase to form folds. This phenomenon increases steel surface roughness: the more intense the peritectic reaction, the greater is the surface roughness.…”
Section: Resultsmentioning
confidence: 99%
“…It may depend on the large surface roughness of peritectic steel. The research of Guo [ 27 ] showed that during the solidification of steel, the peritectic reaction causes the surface shrinkage of the δ phase to form folds. This phenomenon increases steel surface roughness: the more intense the peritectic reaction, the greater is the surface roughness.…”
Section: Resultsmentioning
confidence: 99%
“…В результаті перитектичного перетворення виникає некогерентність меж фаз (до 6%) між δ-феритом та аустенітом; крім того, ці фази мають різну теплопровідність, що сприяє утворенню тріщин під час безперервного лиття [3]. Окрім наведених вище причин, є ще різні пояснення утворення тріщин під час затвердіння криці за безперервного лиття: максимальна термічна усадка зміщується вліво зі збільшенням переохолодження [4]; коли виникає напруження або деформація стиснення затверділої оболонки, що перевищує критичне значення міцности на розрив та інші [1−3]. Під час утворення первинної фази δ-фериту встановлюються сильні поля дифузії розчиненої речовини, що призводить до пригнічення її зародження, а отже, встановлюється температура нижче за рівноважну перитектичну температуру, перш ніж почнеться перитектична реакція [1].…”
Section: вступunclassified
“…Одним із підходів до забезпечення зменшення розтріскування криці є вибір раціонального вмісту леґувальних елементів і вмісту Карбону в криці. Слід зазначити, що за високого вмісту Mn, Al або Si в криці зона співіснування фаз L + δ + γ збільшується [4]. Як відомо, для підвищення механічних властивостей криці використовують леґування Манґаном і Силіцієм.…”
Section: вступunclassified
“…3) In peritectic-steel continuous casting process, longitudinal cracks have always been a serious problem influencing the quality of steel shells, which is mainly caused by a volumetric shrinkage occurring during δ -γ phase transformation. 4) It can be relieved with an application of a "mild cooling" strategy in a mold, especially in the initial stage of solidification. 5) Presently, the main method employed in steel…”
Section: Introductionmentioning
confidence: 99%
“…3. The equation of t 2 follows: .............................. (3)The characteristic time t 2 can be expressed as:18) ...................... (4). …”
mentioning
confidence: 99%